PENGARUH KONSELING ISLAMI SOLUTION FOCUSED BRIEF THERAPY TERHADAP SELF-ESTEEM SISWA MTsN BANTUL KOTA TAHUN 2015/2016 - Kaharja Kaharja; Eva Latipah (Jurnal Pendidikan Agama Islam, 2016)
This research aims to determine infulence of Islamic counseling solution focused brief therapy to selfesteem of students of MTs Negeri Bantul Kota in year of 2015/2016. Research subjects were four students of MTs Negeri Bantul Kota. Counseling to each subject took place in four sessions and each session lasted about 60 minutes. Design of the research was one group pre-test and post-test design (design re-treatment) i.e. by measuring self esteem of students before and after treatment. The measurement is done by using self-esteem scale adoption of self-esteem scale of Copersmith with modifications. Data were analyzed using Wilcoxon (Wilcoxon Signed Range Test). The score of tests were analyzedby using SPSS series 18 for windows.Results showed that Islamic counseling solution focused brief therapy was effective to self-esteem from low category (78,50) into high category (123,50) after treatment. Based on results of analysis, significance value of pre and post-test was 0.046 (p<0.05). It can be concluded that there was effective influence of Islamic counseling solution focused brief therapy to self-esteem. Results of quantitative analysis was that Islamic counseling solution focused brief therapy provided more optimal results when it was given to subjects who had intellectual capacity of average upper and active during therapy in progress.